Three novel mutations in MODY and its phenotype in three different Czech families - Bazalová, Zdenka; Rypáčková, Blanka; Brož, Jan; Brunerová, Ludmila; Polák, J; Rušavý, Zdeněk; Trešlová, Ludmila; Anděl, Michal (Diabetes research and clinical practice, 2010)
AIMS/HYPOTHESIS: MODY (Maturity Onset Diabetes of the Young) is an autosomal dominant inherited type of diabetes with significant genetic heterogeneity. New mutations causing MODY are still being found. A genetically confirmed diagnosis of MODY allows application of individualized treatment based on the underlying concrete genetic dysfunction. Detection of novel MODY mutations helps provide a more complete picture of the possible MODY genotypes. MATERIALS AND METHODS: We tested 43 adult Czech patients with clinical characteristics of MODY, using direct sequencing of HNF1A (hepatocyte nuclear factor 1-alpha), HNF4A (hepatocyte nuclear factor 4-alpha) and GCK (glucokinase) genes. RESULTS: In three Czech families we identified three novel mutations we believe causing MODY-two missense mutations in HNF1A [F268L (c.802T>C) and P291S (c.871C>T)] and one frame shift mutation in GCK V244fsdelG (c.729delG). Some of the novel HNF1A mutation carriers were successfully transferred from insulin to gliclazide, while some of the novel GCK mutation carriers had a good clinical response when switched from insulin or oral antidiabetic drugs to diet. CONCLUSION: We describe three novel MODY mutations in three Czech families. The identification of MODY mutations had a meaningful impact on therapy on the mutation carriers.
Keywords: mutace; hepatocytární jaderný faktor 4; glukokinasa; Glucokinase; Phenotype; gliklazid; Pedigree; výsledek terapie; Československo; rodokmen; dietoterapie; diabetes mellitus; lidé; Hypoglycemic Agents; Mutation; Insulin; Treatment Outcome; hypoglykemika; zdraví rodiny; hepatocytární jaderný faktor 1-alfa; Hepatocyte Nuclear Factor 1-alpha; Family Health; Diabetes Mellitus; Gliclazide; fenotyp; Diet Therapy; Czechoslovakia; inzulin; Hepatocyte Nuclear Factor 4; Humans